Short‐term and long‐term outcomes of interstitial lung disease in polymyositis and dermatomyositis: A series of 107 patients - I. Marie; Pierre‐Yves Hatron; S. Dominique; P. Chérìn; Luc Mouthon; Jean-François Ménard (2011)
This study was undertaken to assess the characteristics and outcome of interstitial lung disease (ILD) in polymyositis/dermatomyositis (PM/DM) and to determine variables predictive of ILD deterioration in PM/DM.Among 348 consecutive patients with PM/DM, 107 patients with ILD were identified by medical records search in 4 medical centers. All patients underwent pulmonary function tests (PFTs) and pulmonary high-resolution computed tomography (HRCT) scan.ILD onset preceded PM/DM clinical manifestations in 20 patients, was identified concurrently with PM/DM in 69 patients, and occurred after PM/DM onset in 18 patients. Patients with ILD could be divided into 3 groups according to their presenting lung manifestations: patients with acute lung disease (n = 20), patients with progressive-course lung signs (n = 55), and asymptomatic patients with abnormalities consistent with ILD evident on PFTs and HRCT scan (n = 32). We observed that 32.7% of the patients had resolution of pulmonary disorders, whereas 15.9% experienced ILD deterioration. Factors that predicted a poor ILD prognosis were older age, symptomatic ILD, lower values of vital capacity and diffusing capacity for carbon monoxide, a pattern of usual interstitial pneumonia on HRCT scan and lung biopsy, and steroid-refractory ILD. The mortality rate was higher in patients with ILD deterioration than in those without ILD deterioration (47.1% versus 3.3%).Our findings indicate that ILD results in high morbidity in PM/DM. Our findings also suggest that more aggressive therapy may be required in PM/DM patients presenting with factors predictive of poor ILD outcome.